Practical approaches to biological inorganic chemistry - Crichton, Robert R.; Louro, Ricardo O. (Elsevier, 2013)
The book reviews the use of spectroscopic and related methods to investigate the complex structures and mechanisms of biological inorganic systems that contain metals. Each chapter presents an overview of the technique including relevant theory, clearly explains what it is and how it works and then presents how the technique is actually used to evaluate biological structures. Practical examples and problems are included to illustrate each technique and to aid understanding. Designed for students and researchers who want to learn both the basics, and more advanced aspects of bioinorganic chemistry. Many colour illustrations enable easier visualization of molecular mechanisms and structuresWorked examples and problems are included to illustrate and test the reader's understanding of each techniqueWritten by a multi-author team who use and teach the most important techniques used today to analyse complex biological structures.